Pengaruh Pertimbangan Pasar Kerja, Kecerdasan Adversitas, Efikasi Diri, dan Nilai Sosial terhadap Minat Menjadi Akuntan Publik - Ramadhani, Mutiara Diva; Mimba, Ni Putu Sri Harta (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The study aims to identify the influence of job market considerations, adversity intelligence, self-efficacy, and social values ​​on interest in becoming a public accountant. The research population was 226 accredited undergraduate accounting students at state universities in Bali, class of 2020. Data was collected through a survey using probability sampling and simple random sampling techniques with a partial least square-based structural equation modeling (SEM-PLS) approach. The results show the job market considerations, adversity intelligence, self-efficacy, and social values ​​have a significant positive effect on interest in becoming a public accountant. The higher the independent variables, the interest in becoming a public accountant will increase.